If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c = 36(n + 16) Reorder the terms: c = 36(16 + n) c = (16 * 36 + n * 36) c = (576 + 36n) Solving c = 576 + 36n Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Simplifying c = 576 + 36n
| (5x+6y)(5x-6y)=0 | | 8=2(x-2) | | 45=9f | | 5x+6x=-11 | | X^3-3x^2-9x+3=0 | | (4x-5)(3-2x)=12-9(2x-5) | | 9+2+4=183652 | | 3(5x+6x)=108 | | 4x-72=-36 | | 4(x-14)=160 | | 4t+20-15= | | y=-4x^2+2x-3 | | 0=x^2+20x+208 | | 0=x^2+20+208 | | 40=2x+5+2x-3 | | tanx=0.5714 | | 3x+5(6.5)=37 | | 7(5y-4)=21y | | er^10=2er^1 | | x+3+2(x-4)=28 | | 14n^2+14n=0 | | 0.25x+3.5=20 | | 2k+6=11 | | 0.25x+3.5=0 | | 3(-y+8)+5y=37 | | 3(3+5m)-12+(-3m)= | | 4b-2+7b=20 | | 19-(x+8)=6x+3 | | -4y/4= | | 2(5)-3y=9 | | 2x-3y=y | | 2x-3y=p |